MTCH2-mediated mitochondrial fusion drives exit from naïve pluripotency in embryonic stem cells. Issue 1 (December 2018) - Bahat, Amir; Goldman, Andres; Zaltsman, Yehudit; Khan, Dilshad; Halperin, Coral; Amzallag, Emmanuel; Krupalnik, Vladislav; Mullokandov, Michael; Silberman, Alon; Erez, Ayelet; Schimmer, Aaron; Hanna, Jacob; et al.
Abstract The role of mitochondria dynamics and its molecular regulators remains largely unknown during naïve-to-primed pluripotent cell interconversion. Here we report that mitochondrial MTCH2 is a regulator of mitochondrial fusion, essential for the naïve-to-primed interconversion of murine embryonic stem cells (ESCs). During this interconversion, wild-type ESCs elongate their mitochondria and slightly alter their glutamine utilization. In contrast, MTCH2 −/− ESCs fail to elongate their mitochondria and to alter their metabolism, maintaining high levels of histone acetylation and expression of naïve pluripotency markers. Importantly, enforced mitochondria elongation by the pro-fusion protein Mitofusin (MFN) 2 or by a dominant negative form of the pro-fission protein dynamin-related protein (DRP) 1 is sufficient to drive the exit from naïve pluripotency of bothMTCH2 −/− and wild-type ESCs. Taken together, our data indicate that mitochondria elongation, governed by MTCH2, plays a critical role and constitutes an early driving force in the naïve-to-primed pluripotency interconversion of murine ESCs. Reprogramming of mitochondria metabolism occurs during naïve to primed pluripotency differentiation in mouse embryonic stem cells (ESCs). Here the authors show that mitochondrial MTCH2 regulates mitochondrial fusion and that this fusion is required for naïve to primed pluripotency conversion